UNIT 1.12 Developmental Toxicity Assays Using the Drosophila Model. Issue 1 (19th February 2014) - Rand, Matthew D.; Montgomery, Sara L.; Prince, Lisa; Vorojeikina, Daria
Abstract: The fruit fly ( Drosophila melanogaster ) has long been a premier model for developmental biologists and geneticists. In toxicology studies, Drosophila has only recently gained broader recognition as a tool to elaborate molecular genetic mechanisms of toxic substances. In this article, two practical applications of Drosophila for developmental toxicity assays are described. The first assay takes advantage of newly developed methods to render the fly embryo accessible to small molecules, toxicants, and drugs. The second assay engages straightforward exposures to developing larvae and easy‐to‐score outcomes of adult development. With the extensive collections of flies that are publicly available and the ease of creating transgenic flies, these two assays have a unique power for identifying and characterizing molecular mechanisms and cellular pathways specific to the mode of action of a number of toxicants and drugs. Curr. Protoc. Toxicol . 59:1.12.1‐1.12.20. © 2014 by John Wiley & Sons, Inc.